2017
DOI: 10.1016/j.cgh.2016.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vedolizumab Induction and Maintenance Therapy in Patients With Ulcerative Colitis, Regardless of Prior Exposure to Tumor Necrosis Factor Antagonists

Abstract: Vedolizumab demonstrated significantly greater efficacy as induction and maintenance therapy for UC than placebo in patients naive to TNF antagonists and patients with TNF antagonist failure. There were numerically greater treatment differences at Week 6 among patients receiving vedolizumab who were naive to TNF antagonists than patients with TNF antagonist failure. ClinicalTrials.gov no: NCT00783718.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
143
1
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 37 publications
(41 reference statements)
15
143
1
12
Order By: Relevance
“…They consistently showed benefit from vedolizumab treatment in the induction and maintenance of clinical response and remission in both anti‐TNF failure and anti‐TNF naïve patients, in comparison with placebo. Authors observed that the rates of response and remission were higher in CD patients not exposed to anti‐TNF agents than in patients who had anti‐TNF failure . These higher rates persisted at week 52.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They consistently showed benefit from vedolizumab treatment in the induction and maintenance of clinical response and remission in both anti‐TNF failure and anti‐TNF naïve patients, in comparison with placebo. Authors observed that the rates of response and remission were higher in CD patients not exposed to anti‐TNF agents than in patients who had anti‐TNF failure . These higher rates persisted at week 52.…”
Section: Discussionmentioning
confidence: 99%
“…A question arises about the impact of previous exposure to anti‐TNF drugs on vedolizumab efficacy. Two post hoc analyses from the GEMINI studies evaluated the efficacy of vedolizumab in CD and UC based on prior anti‐TNF exposure . They consistently showed benefit from vedolizumab treatment in the induction and maintenance of clinical response and remission in both anti‐TNF failure and anti‐TNF naïve patients, in comparison with placebo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the subanalysis focusing on the type of IMM, the median TLs were not influenced, irrespective of the IMM, methotrexate or thiopurin. At week 2, the median TLs were measured at 29 (24.5-37) and 30 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) µg/ml with thiopurin and methotrexate, respectively (P = 0.6). At week 6, the median TLs were measured at 27 (17.5-38.5) and 22 (16.3-37.5) µg/ml with thiopurin and methotrexate, respectively (P = 0.6).…”
Section: Impact Of Immunomodulator On Vedolizumab Trough Level At Indmentioning
confidence: 99%